2019
DOI: 10.3390/ijms20205216
|View full text |Cite
|
Sign up to set email alerts
|

Disinfection and Sterilization Using Plasma Technology: Fundamentals and Future Perspectives for Biological Applications

Abstract: Recent studies have shown that plasma can efficiently inactivate microbial pathogens such as bacteria, fungi, and viruses in addition to degrading toxins. Moreover, this technology is effective at inactivating pathogens on the surface of medical and dental devices, as well as agricultural products. The current practical applications of plasma technology range from sterilizing therapeutic medical devices to improving crop yields, as well as the area of food preservation. This review introduces recent advances a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
212
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 235 publications
(216 citation statements)
references
References 101 publications
(149 reference statements)
1
212
0
3
Order By: Relevance
“…Thus, reactive chemical species such as OH and H radicals may act to eliminate bacteria by oxidizing biomolecules. Indeed, these findings are consistent with a previous study that showed that the OH radical is the most important factor for bacterial inactivation during plasma treatment [ 16 , 30 ]. Thus, oxidation and degradation of biomolecules may be caused by reactive chemical species such as reactive nitrogen species (RNS) and reactive oxygen species (ROS) generated by the plasma.…”
Section: Discussionsupporting
confidence: 93%
“…Thus, reactive chemical species such as OH and H radicals may act to eliminate bacteria by oxidizing biomolecules. Indeed, these findings are consistent with a previous study that showed that the OH radical is the most important factor for bacterial inactivation during plasma treatment [ 16 , 30 ]. Thus, oxidation and degradation of biomolecules may be caused by reactive chemical species such as reactive nitrogen species (RNS) and reactive oxygen species (ROS) generated by the plasma.…”
Section: Discussionsupporting
confidence: 93%
“…Cold atmospheric plasma (CAP) is a promising technology for medicine, sterilization, and surface and water treatment. CAP has bactericidal, fungicidal, and sporicidal effects, [ 1–4 ] as well as a selective toxic effect on tumor cells. [ 5,6 ] It also stimulates proliferation of keratinocytes [ 7 ] and fibroblasts, [ 8,9 ] which leads to accelerated wound healing.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past 20 years, various studies have reported the microbicidal effect of plasma including inactivation of prions [ 28 ]. For example, Jalak et al reported the disinfection of scrapie prions by corona discharge in open air [ 29 ], confirming a decrease in both PrP Sc and PrP C by cell infectivity assay and Western blot analysis.…”
Section: Discussionmentioning
confidence: 99%